From beneficiaries to knowledge producers: citizen science and community-led climate adaptation in coastal Indonesia - Farhan (Indonesian Journal of Applied Community Research, 2026)
Background: Coastal communities in Indonesia increasingly face tidal flooding, shoreline change, mangrove pressure, drainage disruption, and livelihood insecurity, yet residents’ everyday knowledge of these risks often remains outside formal adaptation planning. Objective: This community engagement program aimed to transform coastal residents in Pesisir and Klaseman, Probolinggo, from passive beneficiaries of climate assistance into citizen knowledge producers capable of observing, documenting, validating, and communicating local climate evidence. Method: This program applied a participatory citizen science model through partner coordination, needs assessment, climate literacy orientation, observation training, participatory mapping, field monitoring, community validation, micro-adaptation action, and sustainability planning. Results: This program prepared a community-based monitoring architecture involving village actors, fishers, aquaculture workers, women’s groups, youth, environmental cadres, and university facilitators. This program produced observation instruments, participatory risk maps, photo logs, livelihood narratives, validated risk themes, adaptation priorities, and a local monitoring schedule for continued community use. Implication: This program also strengthened residents’ practical capacity to convert lived experience of coastal risk into locally discussable evidence for village-level adaptation. Novelty: The novelty of this program lies in integrating citizen science, local ecological knowledge, and community-led adaptation into an empirically grounded empowerment model that treats coastal residents as producers, validators, and users of climate knowledge.